The Utilization of Information and Communication Technology In Online History Learning In The Pandemic Era of COVID-19 (Descriptive Study: History Education Student) - Gazali Far Far; Rina Pusparani; Wa Ima (Universitas Muhammadiyah Mataram, 2020)
The purpose of this study is to find out about online history learning for Pattimura University students in the Covid-19 Pandemic era. The research method used in this study is a qualitative description. By analyzing directly about the online lecture process for historical education students of FKIP Unpatti Ambon. Based on the results of the research obtained, it can be described as follows: 1.History learning is usually carried out face-to-face in rooms and fields (historical sites) but to prevent the spread of Covid 19, learning is carried out online. 2. Online lectures for Pattimura University students in the Covid 19 Pandemic Era, namely, FKIP Unpatti history education students are required to take part in an online lecture process in order to break the chain of Covid 19 spread